The Noncentral Version of the Whitney Numbers: A Comprehensive Study - Mahid M. Mangontarum; Omar I. Cauntongan; Amila P. Macodi-Ringia (International Journal of Mathematics and Mathematical Sciences)
This paper is a comprehensive study of a certain generalization of Whitney-type and Stirling-type numbers which unifies the classical Whitney numbers, the translated Whitney numbers, the classical Stirling numbers, and the noncentral Stirling (or r-Stirling) numbers. Several identities, applications, and occurrences are also presented.